ROLE OF EBSELEN, A SELENOORGANO COMPOUND IN CISPLATIN INDUCED NEPHROTOXICITY IN WISTAR RATS - M., Praharsheta A.; Samuel, Vanitha; P., Nirmala (International Journal of Current Pharmaceutical Research, 2015)
Objective: Nephrotoxicity is encountered worldwide, irrespective of several factors, but drug induced nephrotoxicity is a complication that is attributed to the high dose and even low dose of drugs. Cisplatin, a platinum complex used in the chemotherapy of several solid tumors was found to have a chief dose limiting side effect namely nephrotoxicity, which occurred due to lipid peroxidation and formation of reactive oxygen species. Ebselen, a eleno organo compound, a glutathione peroxidase mimic with anti-oxidant activity was used in our study to evaluate its nephro protective potential. Methods: Male wistar rats, 6-8 wks old, weighing 180-200 grams were used for the study, which was carried out for a period of 7 wks. Animals were divided into five groups; each group consisting of 6 animals. Group I served as control. Group IV & V received the test drug Ebselen in doses of 10 mg/kg & 20 mg/kg respectively. Group III received Amifostine at 50 mg/kg. The drugs were administered once a week intraperitoneally for 5 wks. Nephrotoxicity was induced at a dose of 5 mg/kg single dose for groups II to V in the 6th wk and the drugs in group III, IV & V continued for 5 days post induction. In the 7th wk blood samples were collected for biochemical analysis and kidney tissues for histopathological study. Results: The serum urea, creatinine levels were significantly increased in Cisplatin group compared to other groups. The estimation of antioxidant levels (catalase, superoxide dismutase and glutathione peroxidise) was significantly decreased in cisplatin group and increased in other groups. The estimation of Malondialdehyde an indicator of lipid peroxidation was significantly increased in group II and decreased in drug treated group. Histopathology results of animals treated with Cisplatin showed inflammatory changes such as tubular degeneration, edema, and necrosis, infiltration of cells in tubular interstitum, mild intertubular hemorrhage and atrophy of glomeruli which was severe in group II. Some changes were also observed in Group III, IV and V animals but with less severity. Conclusion: The result of our study effectively proves the antioxidant potential of Ebselen in ameliorating Cisplatin induced nephrotoxicity.